A new approach to the stability problem of plates subjected to arbitrary complex loading - Bich, Dao Huy (Vietnam Journal of Mechanics, 1992)
The pre-buckling and post-buckling deformation processes are assumed to be less complicated, i.e. processes of average curvature, the influence of complex loading on the stability of plates was analyzed in [1]. In this paper eliminating this restriction, post buckling process may be arbitrary complicated, a generalized expression for determining critical force is formulated by Bubnov-Galiorkin's method and loading parameter method.